Physiological, biochemical, and ultrastructural characterization of selenium toxicity in cowpea plants - Silva, Vinícius Martins; Boleta, Eduardo Henrique Marcandalli; Lanza, Maria Gabriela Dantas Bereta; Lavres, Jose; Martins, Juliana Trindade; Santos, Elcio Ferreira; dos Santos, Flávia Lourenço Mendes; Putti, Fernando Ferrari; Junior, Enes Furlani; White, Philip J.; Broadley, Martin R.; de Carvalho, Hudson Wallace Pereira; et al. (Elsevier, 2018)
Selenium (Se) is considered a beneficial element for plants; however, in high concentrations, it causes negative effects on plant physiology and development. This study reports the first physiological, nutritional, and ultrastructural description of Se toxicity in cowpea growing under field conditions. Selenium was supplied as a foliar application of sodium selenite at varying concentrations (0, 50, 100, 200, 400, 800, 1200, and 1600 g ha−1). An increased yield was observed with the application of 50 g ha−1 Se. Application of concentrations higher than 50 g ha−1 caused leaf toxicity. Increased lipid peroxidation and hydrogen peroxide concentration and reduced total sugars, sucrose, and carotenoid concentration were observed at highest doses tested (1200 and 1600 g ha−1). Applications of more than 50 g ha−1 Se reduced the phloem diameter, caused chlorosis of the leaf blade with a coalescence of lesions, and caused pink salt deposits to appear. Lesions were observed mainly near the trichomes on the adaxial surface of the leaf blade. An analysis of the element distribution with microprobe X-ray fluorescence spectrometry (μ-XRF) revealed accumulation of Se, calcium (Ca), potassium (K), copper (Cu), and manganese (Mn) near the primary vein and in the necrotic brown areas of the leaf lesions. In contrast, Na was homogeneously distributed in the leaf tissue.